Tigecycline pharmacodynamics in the hollow fiber system of Mycobacterium avium-complex lung disease and the utility of MICs and time-kill studies in drug development - Deshpande, Devyani; Srivastava, Shashikant; Gumbo, Tawanda (Frontiers in Pharmacology, 2025)
BackgroundGuideline-based therapy (GBT) drugs for Mycobacterium avium-complex (MAC) lung disease (LD) were chosen in part because they have low minimum inhibitory concentrations (MICs). Despite these low MICs, GBT achieves 6-month sustained sputum culture conversion in only 43% of patients.MethodsFirst, we co-incubated tigecycline with MAC for 7 days in time-kill studies and calculated the exposure mediating 50% of maximal effect (Emax), or EC50. Next, we performed tigecycline exposure-effect studies in the hollow fiber system of MAC (HFS-MAC) inoculated with the reference ATCC#700898 isolate. Third, we performed an exposure-effect study in the HFS-MAC inoculated with five clinical isolates. Finally, the target exposure (EC80) was used to identify a clinical dose of inhaled tigecycline for MAC-LD in 10,000 virtual subject Monte Carlo experiments (MCE).ResultsIn time-kill studies, the EC50 was 0–24 h area under the concentration-time curve-to-MIC (AUC0–24/MIC) of 174 for extracellular and 4.56 for intracellular MAC (p < 0.001). In the HFS-MAC inoculated with ATCC#700898, the EC50 statistically differed between sampling days. However, studies with five different isolates demonstrated a stable and robust day-to-day EC50 (%CV = 18.18%), with an EC80 AUC0–24/MIC of 33.65. The Emax was 4.84 log10 CFU/mL. In MCE, tigecycline inhalational doses of 35–40 mg/day achieved the EC80 target in >90% of virtual patients, with an MIC breakpoint of 256 mg/L.ConclusionInstead of static time-kill studies with a reference strain, inclusion of multiple MAC isolates in HFS-MAC studies improves the precision of pharmacokinetic/pharmacodynamic parameter estimates. Tigecycline administered via the inhalational route could contribute to the treatment of MAC-LD.